Kategoria porozumień zakazanych ze względu na cel w unijnym oraz polskim prawie ochrony konkurencji - Turno, Bartosz (Kwartalnik Prawa Publicznego, 2012)
Article 101 section 1 of the Treaty on the Functioning of the European Union as well as Article 6 section 1 of the Act on Competition and Consumer Protection prohibits all agreements between undertakings having as their object or effect the prevention, restriction or distortion of competition. It is being claimed that the meaning and scope of the prohibition of the anticompetitive agreement is identical in UE law and Polish law. The same is being rightly said with respect to the terms “an undertaking” and “an agreement”. Although the content of Article 101 section 1 of the TFEU and Article 6 section 1 of the Act is the same the query is: does the prohibition of object restrictions as established in these articles have exactly the same meaning? Is the prohibition of object restrictions understood and applied in the same way by the Commission and the President of the Office for Competition and Consumer Protection (hereafter “the OCCP President”)? The subject matter of this paper is to show that regardless of the same content of the above mentioned provisions of law, the ban on object restrictions is understood and applied differently in the UE law (by the Commission and EU courts) and in Polish law (by the OCCP President and national courts). It seems that the OCCP President, unlike EU Institutions, attaches too much importance to the subjective intention and aim of the parties to the agreement rather than to the object of the agreement. Therefore, such a practice cannot be considered as being in compliance with the economic approach to application of the prohibition of agreements restricting competition.